The Role of Wing Pigmentation, UV and Fluorescence as Signals in a Neotropical Damselfly - Guillermo-Ferreira, Rhainer [UNESP]; Therézio, Eralci M.; Gehlen, Marcelo H.; Bispo, Pitágoras da Conceição [UNESP]; Marletta, Alexandre (Springer Nature, 2013)
Pigmentation patterns, ultraviolet reflection and fluorescent emission are often involved in mate recognition and mate quality functions in many animal taxa. We investigated the role of wing ultra-violet reflection, fluorescence emission, and pigmentation on age and sexual signals in the damselfly Mnesarete pudica. In this species, wings are sexually dimorphic in colour and exhibit age dependency: males and females show a smoky black colouration when young, turning red in mature males while it turns brown in females. First, we investigated wing UV patterns through reflectance and emission spectra. Second, behavioural experiments were undertaken to show male and female responses to manipulated wing pigmentation and experimentally reduced UV (UV-). Reflectance spectra of the wings of juvenile and mature males and females were used to show the differences between controls and individuals with manipulated colouration used in the behavioural experiment. UV-reduced, females with wings painted red, and control males and females were tethered and presented to conspecific males and females, and their behavioral responses were recorded. The male red wing pigmentation and females with red wings elicited an aggressive response in territorial males and a sexual response in females. Both males and females showed neutral responses towards individuals with reduced UV. Wing signals of juvenile individuals also provoked neutral responses. These results suggest that UV, together with pigmentation, plays a role during mate recognition in males and females. Other than butterflies and spiders, it seems that fluorescence signals and UV reflectance can also be part of communication in odonates. © 2013 Springer Science+Business Media New York.
Keywords: Calopterygidae; colouration; Odonata; Sexual selection; structural colour; territoriality